2019
DOI: 10.9778/cmajo.20180066
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perceptions of obesity prevention during infancy: a qualitative study

Abstract: Background: Infancy appears to be a critical period for establishing a person's weight set point. It remains unclear which interventions during infancy may be most effective in preventing later obesity and which ones are most acceptable to parents. The aim of this study was to examine the attitudes of parents of children aged 2 years and under toward different obesity prevention messages and their preferences with regard to these messages. Methods: Using a qualitative research design, we conducted semistructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…The principles of the SB/ST guidelines were commended [ 35 , 45 ] however the majority of end-users reported that meeting the SB/ST guidelines was unrealistic [ 31 , 35 37 , 41 , 42 , 55 ] and only half (51%) of pediatricians thought they were very realistic [ 57 ]. Parents often relied on the benefits of SB/ST such as its use as a “babysitter” to occupy children while parents complete household chores, using the stroller to transport children to where they can be active, improving family communication, regulating behaviour, and using it for educational programming [ 32 , 35 37 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The principles of the SB/ST guidelines were commended [ 35 , 45 ] however the majority of end-users reported that meeting the SB/ST guidelines was unrealistic [ 31 , 35 37 , 41 , 42 , 55 ] and only half (51%) of pediatricians thought they were very realistic [ 57 ]. Parents often relied on the benefits of SB/ST such as its use as a “babysitter” to occupy children while parents complete household chores, using the stroller to transport children to where they can be active, improving family communication, regulating behaviour, and using it for educational programming [ 32 , 35 37 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…End-users liked the simplicity and clarity of the guidelines [ 37 , 42 , 52 , 55 ] although many thought that the PA guidelines were too general (i.e., one-size-fits-all) [ 32 , 34 , 42 ]. Both end-users and stakeholders reported that the guidelines should be more tailored to developmental stage, physical ability, [ 32 , 36 , 52 , 55 ] and socioeconomic status [ 42 , 55 ]. End-users preferred when guidelines were broken down into more achievable steps that could be built upon [ 32 , 34 36 , 42 , 52 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations